2001
DOI: 10.1046/j.1365-2788.2001.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer screening for older women with intellectual disability living in community group homes

Abstract: Breast cancer is one of the commonest cancers to affect women. Present health service guidelines call for screening and mammography for all women aged between 50 and 65 years in an effort to increase early detection and improve survival rates. Nulliparity is one of the associated risk factors for breast cancer. Women with intellectual disability (ID) are increasing in longevity and are frequently nulliparous, and therefore, they are at increased risk of developing breast cancer. The aim of the present study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
94
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 5 publications
(6 reference statements)
3
94
0
Order By: Relevance
“…Disparities in screening for women with physical 30 -32 and intellectual disabilities also exist and have received less attention. Only approximately one-third of eligible women with ID were screened for breast cancer in 2 regional samples from England 33 and Australia. 34 In the Australian study, women were less likely to be screened if they were unmarried, lived in an urban setting, had severe ID, or had concomitant physical disabilities.…”
Section: Breast Cancer Screeningmentioning
confidence: 99%
“…Disparities in screening for women with physical 30 -32 and intellectual disabilities also exist and have received less attention. Only approximately one-third of eligible women with ID were screened for breast cancer in 2 regional samples from England 33 and Australia. 34 In the Australian study, women were less likely to be screened if they were unmarried, lived in an urban setting, had severe ID, or had concomitant physical disabilities.…”
Section: Breast Cancer Screeningmentioning
confidence: 99%
“…Reasons not to attend screening include lack of encouragement by physicians (Grady et al 1992;Nosek & Howland 1997;Miller et al 1998;George 2000), lack of perceived risk (Orton et al 1991;George 2000;Speedy & Hase 2000), fear (Thompson et al 1997), embarrassment (Orton et al 1991;Nosek & Howland 1997), inconvenience (Speedy & Hase 2000), insensitivity of health care workers (Nosek & Howland 1997;Thompson et al 1997;Williams et al 1997), pain or discomfort (Keemers-Gels et al 2000;Andrews 2001;Sapir et al 2003), physical disability (Nosek & Howland 1997), residence in a nursing home and dementia (Marwill et al 1996). Women with intellectual disabilities are among the least frequent users of screening mammography (Cowie & Fletcher 1998;Piachaud & Rohde 1998;Davies & Duff 2001), perhaps because the standard recruitment strategies are not suitable. Active recruitment into mammography programs is generally undertaken based on a mailing list derived from various sources such as general medical practitioner (GP) records or the electoral roll (Ballard-Barbash et al 1999), and for many women with intellectual disability these sources may be inappropriate.…”
mentioning
confidence: 99%
“…21 Davies and Duff highlighted that only 52% of eligible women with an intellectual disability were screened following their invitation for breast screening. 10 A study, which reviewed the uptake and knowledge of breast screening programmes in women with intellectual disabilities living in the community, concluded that general practitioners and practice nurses were currently playing very minor roles in breast screening these women. Primary health care professionals may therefore be missing opportunistic health promotion opportunities.…”
Section: Breast Cancer Screeningmentioning
confidence: 99%
“…Since women with intellectual disability are increasing in longevity and are frequently nulliparous, they are at increased risk of developing breast cancer. 10 Depression and intellectual disability Symptoms of depression in intellectual disability patients can differ from those presented by the general population and may include more prominent biological changes of an altered sleep/wake cycle, changes in appetite and weight, and significant diurnal variation in mood. There is also a decline in adaptive functioning in those with intellectual disability who develop a depressive illness.…”
mentioning
confidence: 99%